Hydroelectrolytic and acid-basic alterations on the immediate postoperative liver transplantation: a qualitative review - Martins, Beatriz Costa Nava; Fonseca-Neto, Olival Cirilo Lucena da (Brazilian Journal of Transplantation, 2021)
Introduction: The immediate postoperative period of liver transplantation (LT) is an instable moment that needs control and patient monitoring. Hidroelectrolytic and acid-basic alterations are just one among many complications in the immediate postoperative of LT, but draws the attention, and requiring a quick and correct handling. Purpose: The aim of this review is to assess the main acid-basic and hidroeletrolytic alterations in the immediate postoperative period of patients after LT. Method: This is a review, a qualitative study; the research was performed on the MEDLINE databases, through the National Center of Biotechnology Information, by acessing the Pubmed website. The inclusion criteria were: (1) publications in English, (2) to be an original article or literature review, and (3) to be in agreement with the theme. Results: According to the articles analyzed, around above 70% patients presented metabolic acidosis on the immediate postoperative of LT, associated to hypercloremia. Sodium levels are the most altered, with hyponatremia. On average 20% of patients presented hyperkalemia after LT. Hypocalcemia, hypomagnesemia and hypophosphatemia are frequent in these patients. Conclusion: Metabolic acidosis associated to hypercloremia, hyponatremia, hypocalcemia and hyperkalemia are the most common disorders on the immediate postoperative period of LT.